ACID SPLASH: QISAS PUNISHMENT TO BE IMPOSED AGAINST THE OFFENDER - Mohammed Farid Huzaimi; Jasri Jamal (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2012)
In Islamic countries, there are cases where a court has given punishment to an acid splasher to be punished by acid as well. In 2004, an Iranian woman was blinded with acid by her suitor for turning down his marriage proposal. Four years later, the Iranian court sentenced the offender to be blinded in both eyes for taking away the woman’s sight under the retribution principle permitted under Iran’s Islamic law. This case’s decision has regularly been objected as the punishment seems inhuman. This paper will discuss in detail the nature of the offence and the punishment imposed in Islamic perspective. Terdapat beberapa kasus di negara-negara Islam di mana pengadilan memberikan hukuman pembalasan terhadap terdakwa yang menyiram cairan asam ke tubuh orang lain. Pada tahun 2004, seorang perempuan Iran dibutakan dengan asam oleh peminangnya setelah si perempuan menolak lamaran pria tersebut. Empat tahun setelahnya, pengadilan di Iran memutuskan untuk menghukum pria tersebut dengan hukuman yang sama, yaitu dibutakan dengan asam. Hukuman ini dijatuhkan dengan dasar asas retribusi menurut hukum Islam di Iran. Putusan hakim dalam kasus ini telah menuai kritik karena hukuman tersebut dianggap tidak berperikemanusiaan. Artikel ini akan membahas lebih dalam tentang perbuatan menyiram cairan asam dan hukuman pembalasan menurut perspektif Islam.